A new species of Halichondriidae, Topsentia vaceleti n. sp. (Halichondrida, Demospongiae, Porifera), collected from coralligenous bottoms of the Aegean Sea - Kefalas, Efthimios; Castritsi-Catharios, Jeanne (Zootaxa, 2012)
A new species, Topsentia vaceleti n. sp., was collected from 70m depth, on a coralligenous bed of the Aegean Sea by trawl(sponge fishing gear “gagava”). The specimen is spherical, 8 cm in diameter, with deep surface grooves. It has a totallydisordered choanosome and a tangential ectosomal skeleton, typical of Topsentia, but exhibits a different type of spicula-tion. This species differs from the other members of the genus by possessing both principal oxeas and secondary oxeas,the latter much longer but thinner, bent and in some cases flexuous or twisted. This is the fourth species of Topsentia Berg, 1899 reported from the Mediterranean Sea.